Impact of economic reforms on institutional environment in a transition economy of Kyrgyzstan - Bazarbaeva, R. Sh. (Journal of Economic Research & Business Administration, 2015)
This article tells how the reforms being implemented in Kyrgyzstan impact of a transition economy and describes the major institutional changes, including, change of the role of the state in the economy, change of the new management system legislative framework , change of the institution of property, development of entrepreneurship and market infrastructure institutions. The article reveals such market economy basic institutions development-related problems, as property privatization, price liberalization, formation of banking system, implementation of tax reforms. With reference to the revealed issues and contradictions in the economy reforms process the author concludes that continually moving elements of the institutional environment require continuous improvement, which needs implementation of a package of measures based on institutional and developmental approach. Such approach considers interaction of economic phenomenon with social, political and legal ones and allows to determine patterns and trends of evolutionary changes, relating to formation of a new institutional structure and economic system environment.